The contribution: Case study and teaching note - Halfond, Jay A. (International journal of value-based management, 1990)
Huntington University has depended on its tuition for most of its operations and thus was not prepared for the gift it was about to receive. After considerable discussion at the Board of Visitors meeting of Huntington's School of Management about the importance of ethics in the curriculum, one retiring corporate head, Dan Jordan, challenged the school to make a significant effort to assume responsibility for the ethical qualities of its graduates. Jordan offered the school its largest contribution ever—which he restricted to the area of ethics. The dean of the college of management, Peter McElroy, now faced an enviable problem: how to spend the income from this gift in a way that conformed to the wishes of the donor and best served the needs of his college.